Fostering pre-service teachers' technological pedagogical content knowledge (TPACK): A quasi-experimental field study. (December 2021) - Lachner, Andreas; Fabian, Armin; Franke, Ulrike; Preiß, Judith; Jacob, Leonie; Führer, Carolin; Küchler, Uwe; Paravicini, Walther; Randler, Christoph; Thomas, Philipp
Abstract: Against the backdrop of preparing students for a digitalized future, supporting pre-service teachers' development of technological pedagogical content knowledge (TPACK) has become paramount in pre-service teacher education. Whether and how pre-service teachers' acquisition of TPACK could be supported is still an open question, as previous research predominantly relied on correlational data and/or self-report assessments. Based on previous research, we developed subject-specific versions of a TPACK-module to support the acquisition of TPACK. Further purpose of the TPACK-module was to enhance technology-related motivation, as motivational orientations have been documented to be crucial for technology integration. We evaluated the effectiveness of the module by means of a quasi-experimental field study. Pre-service teachers (N = 208), enrolled in five subjects, attended regular semester courses on subject-matter pedagogies. In half of the courses, we randomly implemented subject-specific TPACK-modules (duration: three weeks), in which pre-service teachers were taught in using technology for subject-matter teaching, whereas the control condition attended the regular courses without the TPACK-module. We found that pre-service teachers in the courses with the TPACK-modules acquired more TPACK than those in the control courses without the TPACK-modules. Significant effects were also obtained for pre-service teachers' technology-related self-efficacy and their perceived support for technology integration. The effectiveness of the TPACK-modules could be explained by the obtained support for technology integration. The findings highlight the central need of adequate support for pre-service teachers' development of technology-related professional knowledge and motivation in teacher education programs. Highlights: We developed a subject-specific intervention to foster pre-service teachers' TPACK. The intervention was based on evidence-based practices of teacher education. Effects were tested in a cluster randomized study in 5 subjects across three weeks. TPACK was measured by test-based instruments. Effects were obtained for TPACK, self-efficacy, and subjective support.